Politik Kekerabatan di Indonesia: Perkembangan dan Implikasi - Vidya Pertiwi; Sugeng Widodo (Bestuurskunde: Journal of Governmental Studies, 2021)
Kinship politics has become an old topic of discussion in all countries that adhere to democracy, even for a democratic example country like America. The phenomenon of kinship politics is also inseparable from democracy in Indonesia. The rise of kinship politics is reflected in the implementation of the 2020 Regional Head Elections. This has caused concern from various groups, from the general public to democracy experts. They assume that the practice of kinship politics will harm political developments in Indonesia. Based on this phenomenon, this article aims to review kinship politics in the 2020 Regional Head Elections. The review covers implementing kinship politics, the reasons for the widespread practice of kinship politics in Indonesia, and its implications for governance practices in Indonesia. The methodology used is the method of literature study or literature review. Based on the findings, kinship politics in Indonesia occurs in almost all regions in Indonesia and strengthens in the 2020 Regional Head Elections. This happens because of the pattern of patron-client. Furthermore, negative implications are found in a patronage network that leads to cases of KKN-the Indonesian acronym for corruption, collusion, and nepotism, the destruction of local democracy, and moral hazard problems. The alternative used is political party reform, where the party applies a transparent and merit-based mechanism for regeneration.